Posterior Reversible Encephalopathy Syndrome. Issue 2 (March 2018) - Sundin, Courtney Stanley; Johnson, Michelle Laurane
Abstract : Abstract: Posterior reversible encephalopathy syndrome (PRES) is a newly defined syndrome; therefore, this transient clinical condition is not well known and probably underdiagnosed. It develops quickly with symptoms that are usually indistinguishable from eclampsia. Nurses need to be knowledgeable and aware of identifying symptoms and appropriate treatment. The condition is thought to share pathophysiology with eclampsia, and it is suggested that endothelial dysfunction combined with hypertension causes disruption in the blood brain barrier resulting in cerebral edema. Seizures develop secondary to cerebral edema, and mark later stages of the disease. Treatment is aimed at reducing blood pressure (BP) with antihypertensive therapy and seizure control with magnesium sulfate. When PRES is treated early, symptoms typically disappear within a few days and imaging studies normalize in several weeks. Permanent brain damage can occur if diagnosis and treatment are delayed. If PRES is suspected, thorough focused assessments and increased communication among the healthcare team are essential for patient care. When pregnant or postpartum women present with elevated BP accompanied with neurologic symptoms, imaging studies should be considered. An exemplar case is presented of a woman with normal prenatal course that is complicated by rapidly developing preeclampsia, eclampsia, and PRES. Abstract : Posterior reversible encephalopathy syndrome is a newly defined syndrome, therefore this transient clinical condition is not well known and probably underdiagnosed. Pathophysiology and symptoms are similar to eclampsia. A review of the syndrome including an exemplar case is presented.